Approximation of the periodical functions of high smoothness by the rightangled Fourier sums - Novikov, O.O.; Rovenska, O.G. (Carpathian Mathematical Publications, 2013)
We obtain asymptotic equalities for upper bounds of the deviations of the right-angled Fourier sums taken over classes of periodical functions of two variables of high smoothness. These equalities in corresponding cases guarantee the solvability of the Kolmogorov–Nikol’skii problem for the right-angled Fourier sums on the specified classes of functions.